DESIGN AND IMPLEMENTATION OF CONVEYOR LINE SPEED SYNCHRONISER FOR INDUSTRIAL CONTROL APPLICATIONS: A CASE STUDY OF CHAMPION’S BREWERIES PLC, UYO (Nigerian Journal of Technology, 2016)
This paper presents the mathematical modeling of a conveyor mechanism for control applications with Champion Breweries PLC as a case study. The electrical and mechanical sections were modeled separately and then integrated to obtain one composite system. Due to the lack of synchronisation of the conveyor line speed and the speed of action of the empty bottle inspection (EBI), and the full bottle inspection (FBI) units at Champion Breweries, there exists the problem of residue left-over in bottles, cracked bottles on the conveyor line and the non-detection of incorrect liquor level in bottles.Therefore a Proportional Integral Derivative(PID) controller was designed to act as a speed synchronizer in order to eliminate the above mentioned problems. http://dx.doi.org/10.4314/njt.v35i3.21